2012
DOI: 10.1136/jclinpath-2011-200424
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and pathological characteristics of isolated aortitis and Takayasu arteritis with ascending aorta involvement

Abstract: Cases of IA tend to have more histologically active inflammation except for a relatively normal erythrocyte sedimentation rate, localised lesions and milder intimal fibrosis than cases of TA. IgG4 abnormality may not be the main cause of IA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…If the inflammation is limited to the adventitia, then the term periaortitis is often employed. In studies involving primarily the thoracic aorta, noninfectious aortitis has been reported to involve from 2% to 16% of aortic resections [26,29,30,[47][48][49][50][51][52][53][54][55]. Aortitis is often an unexpected diagnosis at histological examination of surgically resected thoracic aneurysms and dissections, and may be the presenting feature of a systemic vasculitis or may occur in the absence of other clinical signs or symptoms of systemic vasculitis.…”
Section: Noninfectious Aortitis/periaortitismentioning
confidence: 96%
See 1 more Smart Citation
“…If the inflammation is limited to the adventitia, then the term periaortitis is often employed. In studies involving primarily the thoracic aorta, noninfectious aortitis has been reported to involve from 2% to 16% of aortic resections [26,29,30,[47][48][49][50][51][52][53][54][55]. Aortitis is often an unexpected diagnosis at histological examination of surgically resected thoracic aneurysms and dissections, and may be the presenting feature of a systemic vasculitis or may occur in the absence of other clinical signs or symptoms of systemic vasculitis.…”
Section: Noninfectious Aortitis/periaortitismentioning
confidence: 96%
“…In patients below the age of 50, Takayasu arteritis is the most common systemic vasculitis that afflicts the aorta [32,47,49,55,[65][66][67][68][69][70]. Takayasu arteritis primarily involves large elastic arteries, particularly the aorta and arch vessels.…”
Section: Takayasu Arteritismentioning
confidence: 99%
“…In a recent Chinese operation series, patients were younger and mostly male [50]. In an Italian study where diagnosis was made by PET with an isolated 18 FDG uptake to the aorta, 9/11 patients were male and age at diagnosis with a mean of 62 years was considerably below that of a comparative group of RCA patients [51].…”
Section: Isolated Aortitis (Ia)mentioning
confidence: 99%
“…At times, it is histologically compared to giant cell arteritis (GCA) (11). GCA is characterized by patchy areas of medial necrosis with infiltration of lymphocytes and plasma cells (1,2). Our patient did not have any areas of necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…While most forms of aortitis can be linked to a specific cause, patients with idiopathic aortitis (IDA), are asymptomatic and usually diagnosed after surgical removal. The specific pathophysiology is not well understood, but can be strongly associated with tobacco smoking, young age at presentation, and family history of aortic aneurysm (1).…”
Section: Introductionmentioning
confidence: 99%